2006
DOI: 10.1128/jb.00303-06
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofBacillus anthracis-Like Bacteria Isolated from Wild Great Apes from Côte d'Ivoire and Cameroon

Abstract: We present the microbiological and molecular characterization of bacteria isolated from four chimpanzees and one gorilla thought to have died of an anthrax-like disease in Côte d'Ivoire and Cameroon. These isolates differed significantly from classic Bacillus anthracis by the following criteria: motility, resistance to the gamma phage, and, for isolates from Cameroon, resistance to penicillin G. A capsule was expressed not only after induction by CO 2 and bicarbonate but also under normal growth conditions. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
190
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(194 citation statements)
references
References 56 publications
2
190
0
2
Order By: Relevance
“…cereus var. anthracis'' CI, was part of a group of closely related isolates that caused deadly anthrax-like infections in primates in the Côte d'Ivoire in 2001-2002and Cameroon in 2004(Klee et al 2006. The CI strain contained plasmids nearly identical to pXO1 and pXO2 (Klee et al 2010).…”
mentioning
confidence: 99%
“…cereus var. anthracis'' CI, was part of a group of closely related isolates that caused deadly anthrax-like infections in primates in the Côte d'Ivoire in 2001-2002and Cameroon in 2004(Klee et al 2006. The CI strain contained plasmids nearly identical to pXO1 and pXO2 (Klee et al 2010).…”
mentioning
confidence: 99%
“…The ST24, ST34, ST177, and ST427 types are known to be found in food, feces, and the human body (http://pubmlst.org; http://cdc.go.kr) 25,26) . The remaining ST26, ST130, ST219, and ST784 types were reported in soil (http://mlstoslo.uio.no).…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12] 2) Only two single-nucleotide differences appeared to be reliable markers for the specific identification of B. anthracis: a variant at nucleotide position 640 in the plcR gene or at position 1050 in the purA gene.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The main difference between these 672 Virulence Volume 4 Issue 8 species is the presence of unique virulence plasmids. However, data gathered in the last decade have shown that B. cereus strains that contain anthrax-specific pXO-like plasmids exist [7][8][9][10][11][12] which further obscures the much intermixed phylogenetic structure of the B. cereus group. Some PCR-based assays in use for detection of B. anthracis rely on plasmid-encoded targets in conjunction with a chromosomal marker to correctly differentiate pathogenic from apathogenic B. anthracis strains and B. anthracis from non-anthracis Bacillus species, respectively (for a review see ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation